2018
DOI: 10.2174/2589645801812010034
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Axillary Brachial Plexus Block Versus Supraclavicular Block In Emergency Crushed Hand Patients : A Comparative Study

Abstract: Background: The current study focusses on ultrasound guided Brachial Plexus Block (BPB) which plays an important role in patients with hand trauma either in pain control or for surgical intervention. The brachial plexus can be blocked by several techniques but the most commonly used are the Supraclavicular (SCB) and Axillary (AXB) blocks. Objective: To compare the two techniques with regards to the performance time, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…LA medication and volumes are summarized in Appendix S5 . A short-acting LA was used in eleven studies (lidocaine [ 15 , 18 , 19 , 20 , 21 , 22 ], mepivacaine [ 1 , 23 , 24 , 25 , 26 ]), a long-acting LA in eleven studies (bupivacaine [ 16 , 27 , 28 , 29 , 30 ], ropivacaine [ 17 , 31 , 32 , 33 , 34 , 35 ]), and a mixture of short- and long-acting LA in six studies [ 36 , 37 , 38 , 39 , 40 , 41 ]. Volumes and dosage of LA of the ABPB varied widely, with the lowest being 20 mL and the highest being 60 mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LA medication and volumes are summarized in Appendix S5 . A short-acting LA was used in eleven studies (lidocaine [ 15 , 18 , 19 , 20 , 21 , 22 ], mepivacaine [ 1 , 23 , 24 , 25 , 26 ]), a long-acting LA in eleven studies (bupivacaine [ 16 , 27 , 28 , 29 , 30 ], ropivacaine [ 17 , 31 , 32 , 33 , 34 , 35 ]), and a mixture of short- and long-acting LA in six studies [ 36 , 37 , 38 , 39 , 40 , 41 ]. Volumes and dosage of LA of the ABPB varied widely, with the lowest being 20 mL and the highest being 60 mL.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 28 studies, 25 studies reported on surgical anesthesia [1,40]. Only 17 studies involving 1254 participants conducted an evaluation for adequate surgical anesthesia at an interval of 30 min after block completion [16,[18][19][20]22,23,25,27,28,30,31,[33][34][35][36][37]40].…”
Section: Primary Outcome: Adequate Surgical Anesthesia Within 30 Min ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 53 articles were included in this systematic review: 38 hand studies and 15 shoulder studies ( Table S1 , available on the Journal’ s website at www.jhsgo.org ). 18 , 19 , 20 , 21 , 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 These 53 articles comprised 73 discrete, surgery-block combination study groups (54 hand and 19 shoulder groups) and 6,579 total subjects (2,875 hand and 3,704 shoulder subjects; Table 1 ). The large majority of studies in both groups were RCTs (94.4% hand and 78.9% shoulder RCTs); most were single-blind.…”
Section: Resultsmentioning
confidence: 99%
“…While comparing the methods for the ABPB, the success rate has been reported as the most important indicator, showing success rate 95%–100% with ultrasound introduction. [520] Therefore, different indicators are required in comparative studies; the block performance time and the onset time are important indicators apart from success rate. [21]…”
Section: Discussionmentioning
confidence: 99%